Retraction: Synergetic effects of ultrasound combined with Fenton pretreatment that accelerates wasted activated sludge anaerobic fermentation to produce volatile fatty acids. Issue 116 (16th December 2016) - Bao, Hongxu; Zhang, Hao; Yang, Hua; Jiang, Lei; Liu, Yichen; Shen, Manli; Su, Hongzhi; Liu, Wenzong; Wang, Aijie
Abstract : Retraction of 'Synergetic effects of ultrasound combined with Fenton pretreatment that accelerates wasted activated sludge anaerobic fermentation to produce volatile fatty acids' by Hongxu Bao et al., RSC Advances, 2016, DOI: 10.1039/c6ra19028f